What is known from the existing literature about self-management of pessaries for pelvic organ prolapse? A scoping review protocol. Issue 1 (11th January 2022) - Dwyer, Lucy; Dowding, Dawn; Kearney, R
Abstract : Introduction: Pelvic organ prolapse (POP) can be managed with a pessary; however, regular follow-up may deter women from pessary management due to the inconvenience of frequent appointments, as well as preventing pessary users from autonomous decision-making. Pessary self-management, whereby the woman removes and inserts her own pessary may be a solution to these issues. However, there remains a number of uncertainties regarding the potential benefits and risks of pessary self-management. This scoping review aims to map available evidence about the subject of pessary self-management for POP to identify knowledge gaps providing the basis for future research. Methods and analysis: The scoping review will be conducted using the Joanna Briggs Institute scoping review methodology and reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. A search of Medline, CINAHL, Embase and PsycInfo will be undertaken to identify relevant articles which meet the eligibility criteria using the search terms 'pessary' and 'self-management' or 'self-care'. A hand search of the reference list of non-original research identified during the search but excluded, will be conducted for additional publications which meet the inclusion and exclusion criteria. Data relevant to the topic of pessary self-management will be extracted and critical appraisal of all included publications undertaken. Ethics and dissemination: No ethical or Health Research Authority approval is required to undertake the scoping review. However, it has been registered with The Open Science Framework (DOI 10.17605/OSF.IO/DNGCP). The findings will inform future research exploring pessary self-management and be disseminated via both a presentation at a national conference and publications in peer reviewed journals.